Talfeeq in Sunni Islamic Jurisprudence: Classical Debates, Cross-Madhhab Analysis, and Contemporary Applications in Islamic Finance and Family Law - Zafer Ahmad Ganai; Nasir Nabi (International Journal of Religious and Interdisciplinary Studies, 2025)
This article examines talfeeq as a jurisprudential phenomenon in Sunni Islamic law, utilizing units of analysis that include classical fiqh texts, cross-sectarian legal arguments, and contemporary institutional practices carried out by international fiqh institutions. This study aims to analyze the legality of talfeeq, examine the differences in views between Sunni schools regarding its capabilities, and assess its relevance in addressing modern legal, social, and economic challenges. This research employs a qualitative doctrinal method, analyzing primary fiqh sources, the opinions of authoritative scholars, and the resolutions of contemporary fiqh institutions through comparative and thematic approaches. The study's findings show that the majority of classical scholars restrict the practice of talfeeq due to concerns about legal inconsistencies and the weakening of fiqh methodologies. However, some Maliki and Hanafi scholars allow it under certain conditions. In the contemporary context, talfeeq is increasingly accepted, especially within the framework of ijtihad jama'i, especially in the fields of Islamic finance, family law, and pluralistic legal systems. This article contributes by offering a systematic comparative analysis of classical debate and modern practice, clarifying the methodological limits of talfeeq, and positioning it as an instrument for the legitimate adaptation of Islamic law when applied in a measured manner and based on maqāṣid al-sharī'ah.